Coverage, reporting degree and design of the Swedish quality registry for patients born with cleft lip and/or palate - Kristina Klintö; Agneta Karsten; Agneta Marcusson; Anna Paganini; Sara Rizell; Jenny Cajander; Karin Brunnegård; Malin Hakelius; Åsa Okhiria; Petra Peterson; Avni Abdiu; Christina Havstam; et al. (BMC, 2020)
Abstract Background The objective of the Swedish cleft lip and palate (CLP) registry is to promote quality control, research and improvement of treatment, by comparison of the long-term results of surgery, orthodontics and speech from all six Swedish CLP centres. The purpose of the study was to investigate the coverage and reporting degree of the Swedish CLP registry, and to describe the design of the registry and discuss questions of reliability and validity of the data included. Methods All six Swedish CLP centres participate in the registry. All children in Sweden with cleft lip and/or cleft palate, born from 2009 onwards, are included in the registry. Baseline data such as cleft type (ICD-10 diagnosis), heredity, birth weight and additional deformities and/or syndromes, as well as pre-surgical treatment, are recorded at first visit. Data on surgical treatment are recorded continuously. Treatment outcome regarding dentofacial development and speech are recorded at follow-ups at 5, 10, 16 and 19 years of age. Data on dentofacial development are also recorded 1 year after orthognathic surgery. In addition, data on babbling and speech are recorded at 18 months of age. Coverage degree and reporting degree of surgery was assessed by comparison with registrations in the Swedish Central patient registry. Reporting degree of orthodontic and speech registrations at 5 years of age was assessed by comparison with registrations at baseline. Results The average coverage degree for children born 2009 to 2018 was 95.1%. For cleft-related surgeries, the average reporting degree was 92.4%. Average reporting degree of orthodontic registrations and speech registrations at age 5 years was 92 and 97.5% respectively. Conclusion In order to achieve valid and reliable data in a healthcare quality registry, the degree of coverage and reporting needs to be high, the variables included should be limited and checked for reliability, and the professionals must calibrate themselves regularly. The Swedish CLP registry fulfils these requirements.